Analysis of Livelihood Assets of Coconut Farmers in North Halmahera Regency, North Maluku, Indonesia - Munawir Muhammad; Al Barry Rajab; Hasrul A. Marsaoly; Putri Ayu Anggraini (BIOSAINSTEK, 2026)
This study aims to analyze the performance of livelihood assets of coconut farmers in Simau Village, Galela District, North Halmahera Regency. This study was conducted in 2024. The types and sources of data in this study are primary and secondary data. The sampling method used the Yamane formula with a total sample of 45 respondents. The type of research was qualitative with the analysis method used being the asset pentagon to explain how strong the farmers' control over their livelihood assets, namely human capital, natural capital, financial capital, social capital, and physical capital. The results of the analysis show that there are pentagon assets with variations in scale values for each type of capital. Human capital was 6.45, natural capital was 6.81, financial capital was 5.57, social capital was 4.93, and physical capital was 4.07. This analysis provides an important overview of the priorities and allocation of resources that need to be considered in asset management.